Effects of Heavy Metal Accumulation on the Variation of Glutathione S-transferases (GSTs) Activity in some Economic Fishes in Nhue-Day River Basin - Huong, Ngo Thi Thuy; Tuyet, Le Thi; Ha, Le Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: The aim of this study was to investigate the effects of metal accumulation on the variation of glutathione S-transferase (GST) activities in some fishes (Cyprinus carpio L, Hypophthalmichthys molitrix, and Oreochromis niloticus) in Nhue-Day river basin. Samples for analysis were taken four times from September 2012 to July 2013. The heavy metals were deposited mostly in kidney and liver of all studied fishes by the following order: Zn > Cu > Pb > Cd. Their accumulated patterns in tissues are ranked as: liver >> 1 kidney > gill for Cu; accumulation patterns are similar for Zn, Pb and Cd, accumulated more in kidneys than in liver and gills but at the different extents: kidney > liver ≥ gills for Zn; kidney >> liver > gills for Pb, and kidney > liver >> gills for Cd. GSTs activities in tissues of common carp, silver carp and tilapia were in the following order: liver > kidney > gill. Effects of heavy metal bioaccumulation to the variation of GSTs activity in fish tissues are reflected by the correlations between heavy metal bioaccumulation in fish tissues and GSTs activities observed in respective tissues. In general, metal accumulation in fish tissues showed that Nhue-Day river water was polluted with heavy metals and this influences physiological health of fishes which are reflected by the changes of GSTs in fish tissues. The results of this research help to establish background data for management of aquaculture practices and environmental protection of Nhue-Day river basin. Keywords: Nhue-Day river basin, heavy metals, GSTs activity, common carp, silver carp, tilapia .